UMP Gallery - Noor Syahidah, Sabran (Penerbit UMP, 2012)
Research and development activities in Universiti Malaysia Pahang (UMP) have been carried out since 2005 especially in applied research forms that have produced a variety of products with potentials to be commercialised.